2020
DOI: 10.1063/5.0011331
|View full text |Cite
|
Sign up to set email alerts
|

A film-texture driven piezoelectricity of AlN thin films grown at low temperatures by plasma-enhanced atomic layer deposition

Abstract: Simultaneously inducing preferred crystalline orientation with a strong piezoelectric response in polycrystalline aluminum nitride (AlN) thin films by atomic layer deposition is a technical challenge due to the upscaling of the integration of piezoelectric functionalities, such as sensing and actuation, in micro-devices without any poling process. Utilizing low-temperature plasma-enhanced atomic layer deposition (PE-ALD), highly c-axis-oriented AlN films have been prepared with precise control over the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
5
16
0
Order By: Relevance
“…Significant amounts of O, Al, and N in the transition layer are observed, implying that the transition layer is amorphous with Al x O y oxides and a potential oxynitride forms AlO x N y . It is worth noting that a remarkable amount of oxygen is also observed in the AlN film that is coincident with our previous report, showing that about 6 atom % of O was presented in the AlN film. No formation of Ni x O y has been detected.…”
Section: Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Significant amounts of O, Al, and N in the transition layer are observed, implying that the transition layer is amorphous with Al x O y oxides and a potential oxynitride forms AlO x N y . It is worth noting that a remarkable amount of oxygen is also observed in the AlN film that is coincident with our previous report, showing that about 6 atom % of O was presented in the AlN film. No formation of Ni x O y has been detected.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Akiyama et al revealed a significant increase of the full width half maximum of the (002) diffraction peak and a remarkable decrease of the piezoelectric response as the oxygen concentration increased. That could explain why a low piezoelectric coefficient e 31,f of 0.37 C·m –2 was obtained in our films . However, those impurity levels are comparable to those found in the literature. , Minimization of those impurities is really challenging in chemical vapor deposition due to the presence of residual moisture in the reactor chamber and the carrier gases.…”
Section: Results and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Recently, the crystal quality of ALD AlN has been significantly improved using in situ atomic layer annealing (ALA) [30]. Plasma-enhanced (PE)ALD (without ALA) has also produced AlN films with measurable piezoelectric coefficients e 31, f of up to 0.4 C/m 2 [31].…”
Section: Aluminum Nitride Depositionmentioning
confidence: 99%